ANALISIS PENGARUH UPAH BURUH PUPUK TERHADAP POLA KONSUMSI RUMAH TANGGA (Studi Pada PT. Bhanda Graha Reksa Labuahan Badas) - I Nyoman Sutama; Marisa Sutanty; Bany Irwansyah (Pusat Riset dan Publikasi, 2020)
This study aims to know the effect of fertilizer labor wages toward household consumption system at PT. Bhanda Graha Reksa, Labuhan Badas Sub-District. Type of study was associative which aims to know the effect or relationship between the labor wage variable (X) and the household consumption system variable (Y). The populations in this study were fertilizer workers at PT. Bhanda Graha Reksa, Labuhan Badas Sub-District, as many as 30 people. The data analysis techniques used in this research were simple linear regression analysis, t test and coefficient of determination (R2). Data analysis used the SPSS version 16 program. The findings in this study were that there was effect of labor wages toward household consumption system at PT. Bhanda Graha Reksa Labuhan Badas Sub-District. It was indicated by the calculated value of t-value of 17.972 which was higher than t table of 1.701 (17.972>1.701), and at a significance value of 0.000 was lower than the specified confidence level, which was 0.05 (0.00<0.05). The results of the determination coefficient test (R2) obtained that the value of R Square was also supported by the results of the coefficient of determination analysis obtained R2 of 0.920. This means that the ability of the labor wage variable to influence the household consumption system variable was 92.0%, while its remaining of 8% was influenced by other variables which were not examined.